A heritable microduplication encompassing TBL1XR1 causes a genomic sister‐disorder for the 3q26.32 microdeletion syndrome. Issue 8 (2nd June 2017) - Riehmer, Vera; Erger, Florian; Herkenrath, Peter; Seland, Saskia; Jackels, Miriam; Wiater, Alfred; Heller, Raoul; Beck, Bodo B.; Netzer, Christian
Abstract : Recently, a new syndrome with intellectual disability (ID) and dysmorphic features due to deletions or point mutations within the TBL1XR1 gene located in the chromosomal band 3q26.32 has been described (MRD41, OMIM 616944). One recurrent point mutation in the TBL1XR1 gene has been identified as the cause of Pierpont syndrome (OMIM 602342), a distinct intellectual disability syndrome with plantar lipomatosis. In addition, different de novo point mutations in the TBL1XR1 gene have been found in patients with autism spectrum disorders (ASD) and intellectual disability. Here, we report four patients from two unrelated families in whom array‐CGH analysis and real‐time quantitative PCR of genomic DNA revealed a TBL1XR1‐microduplication. Adjacent genes were not affected. The microduplication occurred as a de novo event in one patient, whereas the other three cases occurred in two generations of a second, unrelated family. We compare and contrast the clinical findings in TBL1XR1 microdeletion, point mutation, and microduplication cases and expand the TBL1XR1‐associated phenotypic spectrum. ID, hearing loss, and ASD are common features of TBL1XR1‐associated diseases. Our clinical observations add to the increasing evidence of the role of TBL1XR1 in brain development, and they simultaneously demonstrate that different genetic disease mechanisms affecting TBL1XR1 can lead to similar ID phenotypes. The TBL1XR1‐microduplication syndrome is an intellectual disability/learning disability syndrome with associated incomplete penetrance ASD, hearing loss, and delay of puberty. Its phenotypic overlap indicates that it is a genomic sister‐disorder to the 3q26.32 microdeletion syndrome.